A structured accelerated versus control rehabilitation pathway after anterior cruciate ligament reconstruction using autologous hamstrings demonstrates earlier improvement in physical outcomes without increasing graft laxity: A randomized controlled trial. (May 2022) - Ebert, Jay R.; Edwards, Peter; Joss, Brendan; Annear, Peter T.
Abstract: Objectives: To investigate whether an accelerated rehabilitation pathway could enhance strength and functional symmetry after ACLR, without affecting laxity. Design: Randomized Controlled Trial. Setting: Private rehabilitation clinic. Participants: 44 patients randomized to an 'Accelerated' (n = 22) or 'Control' (n = 22) rehabilitation intervention. Main outcome measures: Graft laxity (primary outcome), isokinetic knee extensor and flexor strength, hop tests, surveys, sport participation, re-injuries and re-operations. Results: No knee laxity differences (p > 0.05) were observed. A significantly greater (p = 0.006) percentage of Accelerated (77.3%) versus Control (59.1%) patients were participating in Level 1 or 2 pivoting sports at 12 months. Greater limb symmetry indices were observed in the Accelerated group for knee extensor strength at 6 (p < 0.0001), 12 (p = 0.010) and 24 (p = 0.005) months, as well as the triple hop at 6 (p = 0.015) and 9 (p = 0.008) months, and the triple crossover hop at 6 (p < 0.0001) and 9 (p = 0.009) months. One ipsilateral re-tear was observed (Control group, 17 months). No differences (p˃0.05) existed in surveys apart from the Anterior Cruciate Ligament Return to Sport after Injury (ACL-RSI) score, better (p = 0.001) in the Accelerated group at 12 months. Conclusions: Accelerated rehabilitation produced earlier improvement in strength and hop LSIs, without increasing graft laxity. Highlights: An accelerated rehabilitation pathway after ACLR did not adversely affect laxity. Accelerated rehabilitation produced earlier improvement in physical performance. Earlier return to pivoting sports was observed with the accelerated pathway.